A NEW SPECIES OF DIPLYCOSIA (ERICACEAE) FROM SOUTH KALIMANTAN, INDONESIA. (1st March 2016) - Wilkie, P.; Argent, G. C. G.
Abstract : A new species, Diplycosia kalimantanensis P.Wilkie & Argent (Ericaceae), collected on an expedition to Gunung Besar in the Meratus mountains, South Kalimantan, is described and illustrated, and a conservation assessment provided.